Maize systems under climate change in sub-Saharan Africa. Issue 3 (17th August 2015) - Tesfaye, Kindie; Gbegbelegbe, Sika; Cairns, Jill E; Shiferaw, Bekele; Prasanna, Boddupalli M; Sonder, Kai; Boote, Ken; Makumbi, Dan; Robertson, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to examine the biophysical and socioeconomic impacts of climate change on maize production and food security in sub-Saharan Africa (SSA) using adapted improved maize varieties and well-calibrated and validated bioeconomic models. Design/methodology/approach – Using the past climate (1950-2000) as a baseline, the study estimated the biophysical impacts of climate change in 2050 (2040-2069) and 2080 (2070-2099) under the A1B emission scenario and three nitrogen levels, and the socioeconomic impacts in 2050. Findings – Climate change will affect maize yields across SSA in 2050 and 2080, and the extent of the impact at a given period will vary considerably between input levels, regions and maize mega environments (MMEs). Greater relative yield reductions may occur under medium and high-input intensification than under low intensification, in Western and Southern Africa than in Eastern and Central Africa and in lowland and dry mid-altitude than in highland and wet mid-altitude MMEs. Climate change may worsen food insecurity in SSA in 2050 through its negative impact on maize consumption and reduction in daily calorie intake. However, international trade has the potential to offset some of the negative impacts. Originality/value – The study calibrated and applied bioeconomic models to estimate the biophysical and socioeconomic impact of climate change on maize production at fine resolution. The results could be used as a baseline to evaluate measures that will be applied to adapt maize to the future climate in SSA.